Dampak Harga dan Kualitas Produk Terhadap Minat Beli di Pasar Modern Kota Ambon - Kaluku, Lulu A; Kakisina, Leunard O; Parera, Weldemina B (Universitas Pattimura, 2025)
This study aims to examine the influence of price and product quality on vegetable purchase intention in modern markets in Ambon City, specifically at the DP Modern Market and the FM Modern Market. The research employed a quantitative approach using a survey of 100 respondents and multiple linear regression analysis. The results indicate that in the DP Modern Market, price has a positive effect on purchase intention, whereas product quality has a negative effect. In contrast, in the FM Modern Market, both price and product quality negatively affect purchase intention. Both variables significantly influence purchase intention simultaneously in both markets. Differences in consumer characteristics shape the patterns of influence. DP consumers perceive premium prices as a symbol of exclusivity, while FM consumers are more price-sensitive and prioritize immediate benefits. These findings highlight the importance of tailoring marketing strategies to specific market segments.